2018
DOI: 10.1002/ange.201802756
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Interfacial pH Variation at Molecular Length Scales Using a Concurrent Non‐Faradaic Reaction

Abstract: We quantified changes in interfacial pH local to the electrochemical double layer during electrocatalysis by using ac oncurrent non-faradaic probe reaction. In the absence of electrocatalysis,n anostructured Pt/C surfaces mediate the reaction of H 2 with cis-2-butene-1,4-diolt of orm am ixture of 1,4-butanediol and n-butanol with selectivity that is linearly dependent on the bulk solution pH value.Weshow that kinetic branching occurs from acommon surface-bound intermediate, ensuring that this probe reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Only the selectivity for B relative to A changes as the pH or electrolyte strength is altered. In addition, our previous mechanistic analysis 31 confirmed that the Pt surface does not catalyze the conversion of A to B. Taken together, these results indicate that the reaction proceeds through the pHindependent rate-limiting formation of a common surfacebound intermediate, I*, followed by pH-dependent kinetic branching to yield A or B (Figure 4a).…”
Section: ■ Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Only the selectivity for B relative to A changes as the pH or electrolyte strength is altered. In addition, our previous mechanistic analysis 31 confirmed that the Pt surface does not catalyze the conversion of A to B. Taken together, these results indicate that the reaction proceeds through the pHindependent rate-limiting formation of a common surfacebound intermediate, I*, followed by pH-dependent kinetic branching to yield A or B (Figure 4a).…”
Section: ■ Introductionsupporting
confidence: 59%
“…Importantly, increasing the electrolyte strength to a Na + concentration of 0.64 (I = ∼0.8 M) or 0.78 M (I = ∼1.0 M) with added NaClO 4 supporting electrolyte (Figure 2a, blue and purple) leads to no change in the pH scaling in product selectivity. 31 Together these data indicate that (a) the selectivity of the probe reaction is highly sensitive to the pH of the electrolyte and that (b) this pH dependence is insensitive to the ionic strength of the electrolyte beyond 0.4 M ionic strength.…”
Section: ■ Introductionmentioning
confidence: 99%
“…26 When the reactions are carried out at a high current density or in electrolytes that have poor buffer action and/or mass transport, the pH near the cathode surface is wellknown to increase compared to the bulk value. 27,28 Although the impact of local conditions on the selectivity of metal electrodes is well recognized, simulated, and reproduced, 18,26,27,29,30 it is still a common practice to test high surface area electrodes in very low buffer capacity solutions. While the surface structure of a catalyst is very important to determine its intrinsic selectivity and activity, the distinction between the effect of surface structure and mass transport effects on the electrocatalytic activity is not explicitly clear and needs to be urgently clarified in order to improve fundamental understanding of reaction mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Proton-coupled electron-transfer (PCET) reactions are central to energy conversion processes across chemical and biological systems. 1−25 These same reactions take place at the surfaces of materials, 26−28 playing a key role in corrosion, 29 sensing, 30,31 and catalysis. 32−37 Consequently, interfacial PCET reactions underlie a wide array of energy conversion technologies, including flow batteries, 38,39 supercapacitors, 40,41 fuel cells, 42−45 and solar fuels devices.…”
Section: ■ Introductionmentioning
confidence: 99%